A novel MXene-based high-performance flexible pressure sensor for detection of human motion. (1st June 2023) - Zhang, Zhidong; Zhang, Qingchao; Zhang, Huinan; Li, Bo; Zang, Junbin; Zhao, Xuefeng; Zhao, Xiaolong; Xue, Chenyang
Abstract: Flexible pressure sensors possess superior conformal ability, great flexibility, and strong biocompatibility than conventional silicon-based sensors, thereby widely used in electronic skin, wearable devices, and robotic tactile sensing, among other fields. However, flexible pressure sensors are still limited by many challenges related to extended linearity and high sensitivity. In this paper, MXene with a loose layered structure was employed to fabricate high-performance flexible piezoresistive sensors comprising polydimethylsiloxane (PDMS) film with cylindrical microstructure, multilayer Ti3 C2 T x -MXene film, and interdigital electrodes. A cylindrical microstructured silicon wafer was designed and processed by deep silicon etching process, and PDMS flexible substrate was obtained by two inversions as the pressure sensing layer. The resulting flexible pressure sensor exhibited excellent performance in terms of excellent sensitivity up to 519 kPa −1 in the large detection range of 0–8 kPa coupled with great linearity, a response time of 62.7 ms, and a recovery time of 62.8 ms. The high sensitivity was associated with the compression of the interlayer spacing of multilayer MXene nanosheets. In addition, a single flexible pressure sensor and integrated array were utilized to detect the human physical signals and quantitative measurements of pressure distributions. Overall, these findings provided experimental verification for the design and manufacturing of highly sensitive and linear flexible pressure sensors.